2005
DOI: 10.1021/jf047897u
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Radioimmunoassay for the Quantitative Determination of 8-Prenylnaringenin in Biological Matrices

Abstract: Seven carboxylic acid haptens of 8-prenylnaringenin (8-PN) were synthesized, coupled to cationized bovine serum albumin, and employed to raise specific antisera in rabbits. Two linkers of different lengths (C3H6COOH and C6H12COOH) were coupled to the C7-OH group and separated into their respective enantiomers yielding the first four haptens. Racemic derivatives with C4'-OH coupled linkers C5H10COOH and C9H18COOH were synthesized carrying a methylated C7-OH. Another racemic C4'-OH hapten (CH2COOH) was prepared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
32
1
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 24 publications
(31 reference statements)
6
32
1
2
Order By: Relevance
“…However, as only one-third of the samples converted IX, interindividual variability in microbial community activity could strongly influence this in vivo conversion. Finally, Schaefer et al (35) noted that urinary 8-PN excretion after beer consumption was slower than expected (up to several days), which could very well be due to delayed conversion of IX into 8-PN in the intestine, followed by absorption and renal excretion. Enterohepatic circulation is another important factor determining the retention of IX and 8-PN.…”
Section: Discussionmentioning
confidence: 90%
“…However, as only one-third of the samples converted IX, interindividual variability in microbial community activity could strongly influence this in vivo conversion. Finally, Schaefer et al (35) noted that urinary 8-PN excretion after beer consumption was slower than expected (up to several days), which could very well be due to delayed conversion of IX into 8-PN in the intestine, followed by absorption and renal excretion. Enterohepatic circulation is another important factor determining the retention of IX and 8-PN.…”
Section: Discussionmentioning
confidence: 90%
“…Phase II metabolites of 8-PN, including glucuronides and sulfate conjugates, have been identified in incubations with human Caco-2 cells and human hepatocytes [24] (see structures in Figure 1). Conjugates of 8-PN were also reported in urine of men after consuming beer or beer spiked with 8-PN [25], but the radioimmunoassay used in this study did not allow for the identification of specific conjugates. However, little information is available concerning the formation of metabolites of 8-PN in vivo.…”
mentioning
confidence: 72%
“…Defatting the serum with hexane prior to extraction as carried out by Bolca et al may help alleviate this problem [49]. Excellent recoveries (> 90%) from serum, urine and fecal cultures were observed for all prenylflavonoids [22,23,50,51], except in the report by Wyns et al [39], who reported recoveries of 78.7% and 74.1% for 8-PN and XN, respectively. SPE was also used for extraction of IX and 8-PN from urine [21] and serum [39].…”
Section: Biological Fluidsmentioning
confidence: 99%
“…Schaefer et al reported a radioimmunoassay (RIA) that used tritiated 8-PN [22]. The monoclonal antibody against 8-PN employed in the final method showed very little crossreactivity against other prenylated flavonoids.…”
Section: Immunoassaysmentioning
confidence: 99%
See 1 more Smart Citation